2017
DOI: 10.3390/su9122219
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pounding Response Considering Structure-Soil-Structure Interaction under Seismic Loads

Abstract: Pounding phenomena considering structure-soil-structure interaction (SSSI) under seismic loads are investigated in this paper. Based on a practical engineering project, this work presents a three-dimensional finite element numerical simulation method using ANSYS software. According to Chinese design code, the models of adjacent shear wall structures on Shanghai soft soil with the rigid foundation, box foundation and pile foundation are built respectively. In the simulation, the Davidenkov model of the soil ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Moreover, the response of each structure in the group was compared to that of the singlestructure-soil system in order to find out whether or not SSSI effects can be of importance [14,15]. Therefore, we defined a variable J to measure the degree of the effects of SSSI, as shown in Equation (1).…”
Section: Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the response of each structure in the group was compared to that of the singlestructure-soil system in order to find out whether or not SSSI effects can be of importance [14,15]. Therefore, we defined a variable J to measure the degree of the effects of SSSI, as shown in Equation (1).…”
Section: Problem Definitionmentioning
confidence: 99%
“…The shortage of land resources has become a major issue to consider due to rapid urbanization. With urban development and population growth, the amount of buildings is more and more intensive [1]. Furthermore, the clear distance between adjacent buildings is generally smaller without the limit of annual probable sunlight hours in the east-west direction.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that SSI has significant influence on the pounding-involved structural response during earthquakes. Li et al (2017) studied the seismic pounding considering the structure-soil-structure interaction effect (SSSI) for a practical project considering pile foundation, box foundation and rigid foundation conditions. A three-dimensional finite element model was constructed utilizing ANSYS software.…”
Section: Introductionmentioning
confidence: 99%
“…Case history on dynamic structure-soil-structure interaction analysis that considers adjacent tall buildings was also provided as a reference. A three-dimensional finite element numerical simulation using ANSYS was carried out by Li et al [16] as per Chinese design code for Shanghai soft soil with the rigid foundation, box foundation, and pile foundation. For simulation, the Davidenkov model of the soil skeleton curve was assumed for soil behavior, and the contact elements with Kelvin model were adopted to simulate pounding phenomena between adjacent structures.…”
Section: Literature Reviewmentioning
confidence: 99%